2006
DOI: 10.1021/bi0610451
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Regulation of a Transiently Assembled ERK2·Ets-1 Signaling Complex

Abstract: ERK2 is a proline-directed protein kinase that displays a high specificity for a single threonine (Thr-38) on the substrate Ets-1, which lies within the consensus sequence 36phi-chi-Thr-Pro39 (where phi is typically a small hydrophobic residue and chi appears to be unrestricted). Thr-38 lies in a long flexible N-terminal tail (residues 1-52), which also contains a second potential phosphorylation site, Ser-26. How Ets-1 binds ERK2 to promote the phosphorylation of Thr-38 while simultaneously discriminating aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 62 publications
(119 reference statements)
4
91
2
Order By: Relevance
“…Recently, the D-site peptide QKGRKPRDLELPLSPSL derived from Elk-1, which binds the DRS of ERK2, was shown to displace Ets-1 from both the activated and unactivated forms of ERK2 (23). We hypothesized that rather than displacing Ets-1 through an allosteric mechanism this peptide directly competes with Ets-1 for the DRS of ERK2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the D-site peptide QKGRKPRDLELPLSPSL derived from Elk-1, which binds the DRS of ERK2, was shown to displace Ets-1 from both the activated and unactivated forms of ERK2 (23). We hypothesized that rather than displacing Ets-1 through an allosteric mechanism this peptide directly competes with Ets-1 for the DRS of ERK2.…”
Section: Resultsmentioning
confidence: 99%
“…Despite lacking a canonical D-site, the substrate Ets-1 is displaced from ERK2 by peptides containing a D-site (23). This suggests that Ets-1 may contain a novel or cryptic D-site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1(B)]. With the exception of Glu142, Val143, Phe166 and the N-terminal Gly-Ser-His-Met tag, almost complete 1 H N , 15 N, 13 C a , 13 C b , and 13 C 0 resonance assignments were obtained for this construct. These chemical shifts were used to identify the secondary structural elements of PntP2 142-252 with the MICS (Motif Identification by Chemical Shift) algorithm.…”
Section: Pointed-p2 Pnt Domain Contains a Dynamic Helix H0mentioning
confidence: 93%
“…10,11 The docking interfaces on the PNT domain and the kinase have been mapped coarsely through mutagenesis, NMR spectroscopic, chemical footprinting, and competition studies. 10,[12][13][14][15] To both accommodate the proposed docking mechanism and position the phosphoacceptors in the catalytic site of the kinase, a significant conformational change in the ETS1 PNT domain, such as the unfolding of the appended Nterminal helix H0 (residues Lys42-Thr52), appears to be required. 16 Indeed, NMR relaxation and amide hydrogen exchange (HX) measurement have shown that this helix is only marginally stable and structurally flexible.…”
mentioning
confidence: 99%